An updated European Organisation for Research and Treatment of Cancer (EORTC) protocol for pathological evaluation of sentinel lymph nodes for melanoma. (June 2019) - Cook, Martin G.; Massi, Daniela; Szumera-Ciećkiewicz, Anna; Van den Oord, Joost; Blokx, Willeke; van Kempen, Léon C.; Balamurugan, Thiagarajah; Bosisio, Francesca; Koljenović, Senada; Portelli, Francesca; van Akkooi, Alexander C.J.
Abstract: The sentinel lymph node (SLN) biopsy is a highly accurate staging procedure and the most important prognostic factor in melanoma patients. The European Organisation for Research and Treatment of Cancer (EORTC) Melanoma Group aimed to design an updated evolved SLN protocol for the histopathological workup and reporting. We herein recommend extending the distance between steps according to the short axis dimension of the lymph node and optimise both conventional sectioning and staining procedures including immunohistochemistry. We also provide guidance on the description of the spatial localisation of melanoma deposits in a SLN. The histopathological features to be reported include the following: presence or absence of the metastasis, the intranodal location of the metastasis (subcapsular, parenchymal, combined, extensive confluent and extensive multifocal), the number of the metastatic deposits (1, 2–5, 6–10, 11–20 and >20), the maximum dimension of the largest metastasis (indicating its site) and the presence of extracapsular extension and of naevus cells. This updated EORTC protocol is expected to clarify and simplify the existing procedures, ensuring a reasonable workload for the laboratory and for the pathologists resulting in cost saving with no loss, and possible increase, in accuracy. Highlights: The updated protocol ensures a reasonable workload for the laboratory and pathologists. Sectioning, staining and reporting procedures are herein described. Deposit location: subcapsular, parenchymal, combined and extensive confluent/multifocal. The number of the metastatic deposits is grouped as: 1, 2–5, 6–10, 11–20 and >20. The maximum dimension of the largest deposit and its site are to be reported.